Engeletin Protects Against TNF-α-Induced Apoptosis and Reactive Oxygen Species Generation in Chondrocytes and Alleviates Osteoarthritis in vivo - Wang H; Jiang Z; Pang Z; Qi G; Hua B; Yan Z; Yuan H (Dove Medical Press, 2021)
Hao Wang,1,* Zengxin Jiang,1,* Zhiying Pang,1 Guobin Qi,1 Bingxuan Hua,1 Zuoqin Yan,1 Hengfeng Yuan2 1Department of Orthopaedic Surgery, Zhongshan Hospital, Fudan University, Shanghai, People’s Republic of China; 2Department of Orthopaedic Surgery, Shanghai Sixth People’s Hospital, Shanghai Jiaotong University, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zuoqin YanDepartment of Orthopaedic Surgery, Zhongshan Hospital, Fudan University, 180 Fenglin Road, Xuhui District, Shanghai, 200032, People’s Republic of ChinaTel +86 13818009668Email yan.zuoqin@zs-hospital.sh.cnHengfeng YuanDepartment of Orthopaedic Surgery, Shanghai Sixth People’s Hospital, Shanghai Jiaotong University, 600 Yishan Road, Xuhui District, Shanghai, 200233, People’s Republic of ChinaTel +86 13917398796Email yuan.hengfeng@hotmail.comPurpose: Osteoarthritis (OA) is a progressive disease characterized by pain and impaired joint functions. Engeletin is a natural compound with anti-inflammatory and antioxidant effects on other diseases, but the effect of engeletin on OA has not been evaluated. This study aimed to elucidate the protective effect of engeletin on cartilage and the underlying mechanisms.Methods: Chondrocytes were isolated from rat knee cartilage, and TNF-α was used to simulate OA in vitro. After treatment with engeletin, the expression of extracellular matrix (ECM) components (collagen II and aggrecan) and matrix catabolic enzymes (MMP9 and MMP3) was determined by Western blotting and qPCR. Chondrocyte apoptosis was evaluated using Annexin V-FITC/PI and flow cytometry. Apoptosis-related proteins (Bax, Bcl-2, and cleaved caspase-3) were evaluated by Western blotting. The mitochondrial membrane potential of chondrocytes was measured with JC-1, and intracellular reactive oxygen species (ROS) levels were determined with DCFH-DA. Changes in signaling pathways (Nrf2, NF-κB and MAPK) were evaluated by Western blotting. In vivo, anterior cruciate ligament transection (ACLT) was used to induce the rat OA model, and engeletin was administered intraarticularly. The therapeutic effect of engeletin was analyzed by histopathological analysis.Results: Pretreatment with engeletin alleviated TNF-α-induced inhibition of ECM components (collagen II and aggrecan) and upregulation of matrix catabolic enzymes (MMP9 and MMP3). Engeletin ameliorated chondrocyte apoptosis by inhibiting Bax expression and upregulating Bcl-2 expression. Engeletin maintained the mitochondrial membrane potential of chondrocytes and scavenged intracellular ROS by activating the Nrf2 pathway. The NF-κB and MAPK pathways were inhibited by treatment with engeletin. In vivo, ACLT-induced knee OA in rats was alleviated by intraarticular injection of engeletin.Conclusion: Engeletin ameliorated OA in vitro and in vivo. It may be a potential therapeutic drug for OA.Keywords: engeletin, osteoarthritis, OA, apoptosis, reactive oxygen species, ROS, mitochondrial membrane potential